Investigating variations of fluorescent dissolved organic matter in wastewater treatment using synchronous fluorescence spectroscopy combined with principal component analysis and two-dimensional correlation. Issue 19 (2nd October 2018) - Pan, Hongwei; Yu, Huibin; Wang, Yanan; Liu, Ruixia; Lei, Hongjun
ABSTRACT: Synchronous fluorescence spectroscopy (SFS) combined with principal component analysis (PCA) and two-dimensional (2D) correlation was applied to investigate removal efficiencies and variations of dissolved organic matter (DOM) fractions in the wastewater treatment plant (WWTP) with an A2O craft. A decreasing order of total removal efficiencies was tyrosine-like fluorescence component (89.58%) > humic-like fluorescence (HLF) component (39.83%) > tryptophan-like fluorescence component (36.89%) > microbial humic-like fluorescence (HLF) component (12.47%) > fulvic-like fluorescence component (6.37%). The tyrosine-like, tryptophan-like and HLF components were deeply decomposed by anaerobic bacteria in the anaerobic zone. The tyrosine-like component was the preponderant fraction of DOM in the raw water and primary sediment tank. The tyrosine-like component was the dominant component of DOM too in the anaerobic and anoxic zones, but its proportion was slightly more than the tryptophan-like component. The tryptophan-like component was the dominant component in the facultative zone, the oxic zone and the secondary sediment tank. Based on the changing band order of 279 → 304 → 490 → 330 → 380 → 430 nm, the decreasing variation order was tyrosine-like > tryptophan-like > humic-like > microbial humic-like > fulvic-like component. Therefore, the SFS combined with PCA and 2D correlation is an effective tool for not only monitoring the removal of DOM components but also characterizing variations of DOM fractions in the WWTP.